Surface modification of graphene nanofillers to improve the thermal and mechanical properties of polybutylene succinate-graphene nanocomposites - Anis Sakinah, Zainal Abidin (2018)
This study investigated the reinforcing effects of alkylated graphene oxide on polybutylene succinate (PBS) matrix to promote homogeneous dispersion and increase the interfacial adhesion between graphene oxide (GO) and nonpolar polymer matrix. Therefore, GO was fabricated and functionalised with octadecylamine (ODA) prior to the incorporation with PBS matrix. The fabrication of GO was realised by oxidation of graphite using different graphite precursors via Hummer’s or Tour’s methods. Amount and types of oxygen-containing functional groups were characterised using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), thermal gravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and Raman spectroscopy. A predictive technique for estimating oxidised carbon ratio from Raman spectra was also developed. In this study, the oxidation of expanded graphite via Hummer’s method (KGO) was chosen for further functionalisation with octadecylamine due to higher percentage of oxidised carbon. The modification of GO with ODA was done via sonochemical reaction. The structure and morphology of the produced graphene oxide/octadecylamine (GOODA) was analysed using atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM), XRD, transmission electron microscopy (TEM), and water contact angle. The successful functionalisation between GO and ODA was further confirmed via XPS, FTIR, and Raman analyses while the thermal properties were investigated with TGA analysis. The analyses showed that the modification of GO was proven successful with the insertion of amine group on GO planes. PBS matrix was grafted with graphene oxide/octadecylamine (GOODA) to produce PBS/GOODA via solution intercalation method. The distribution of filler and morphology was studied via FESEM and XRD. The thermal properties and degree of crystallinity of the nanocomposite were monitored by differential scanning calorimetry (DSC) and TGA. In addition, FTIR was performed for further understanding of the chemical interaction between the GOODA filler and PBS matrix. GOODA did not profoundly affect the crystallinity of PBS/GOODA nanocomposite but interestingly improved the mechanical and thermal properties. The addition of low loading GOODA content in PBS/GOODA nanocomposite exhibit a significant increment of tensile strength and Young’s modulus up to 50% and 58.9%, respectively at 0.1 wt% GOODA loading. The in situ reduction of GOODA by thermal treatment in PBS matrix was also done to study the effect of reduction and restoration of graphene plane on functionalised GO. Thermally treated PBS/GOODA (TTPBS/GOODA) showed a sharp increase in tensile strength and Young’s modulus exhibiting an increment of up to 78% and 96%, respectively from pristine PBS at 0.3 wt% GOODA loading. The improvement in strength and thermal behaviour of both PBS/GOODA and TTPBS/GOODA nanocomposite were attributed to the effective interfacial interaction between PBS and GOODA nanofiller. Design Expert software was used to optimise the filler loading and processing condition on tensile strength of TTPBS/GOODA nanocomposite. Processing parameters interaction was also investigated. The optimum condition was reported at 31 min of heating time, 0.11 wt% of GOODA loading, and 120 min of dispersion time with 38.78 MPa of tensile strength. In summary, the results obtained showed that the incorporation of GOODA in PBS matrix and in situ reduction of GOODA brought significant improvement in mechanical and thermal properties of both PBS/GOODA and TTPBS/GOODA nanocomposite.